Internal migration industries: Shaping the housing options for refugees at the local level - Matthias Bernt; Ulrike Hamann; Nihad El-Kayed; Leoni Keskinkilic (Urban Studies, 2021)
In this article, we focus on ways in which 'internal migration industries' shape the housing location of refugees in cities. Based on empirical studies in Halle, Schwerin, Berlin, Stuttgart and Dresden, we bring two issues together. First, we show how a specific financialised accumulation model of renting out privatised public housing stock to disadvantaged parts of the population has emerged that increasingly targets migrant tenants. With the growing immigration of refugees to Germany since 2015, this model has intensified. Second, we discuss how access to housing is formed by informal agents. While housing is almost inaccessible for households on social welfare, the situation is even worse for refugees. This situation has given rise to a new 'shadow economy' for housing that offers services with dubious quality for excessive fees. Bringing these two issues together, we argue that housing provision to refugees has become a new business opportunity. This has given rise to a broad variety of 'internal migration industries' that provide the housing infrastructure, but also control access to housing. This not only results in new opportunities for profit extraction, but actively shapes new patterns of segregation and the concentration of refugees in particular types of disadvantaged neighbourhoods.
Keywords: 300; gatekeepers; housing market; migration; refugee accommodation; residential segregation